Senecio nemiae (Asteraceae, Senecioneae), a New Species from Sierra Grande in Patagonia (Argentina) - Bartoli, Adriana (2004)
A new species, Senecio nemiae, from Sierra Grande, Río Negro, Argentina, is described and illustrated. Senecio nemiae most closely resembles S. adenotrichius from Chile, but is clearly different by the shorter leaves without auricles and smaller capitula, with a calyculus of few bracts and length shorter than the involucre. A new status, Senecio sect. Senecio ser. Corymbosi subser. Adenotrichi, is also proposed to accommodate this taxon in the previous classification of Senecio for Argentina. Included is a key to those species of Senecio subser. Adenotrichi with glabrous achenes.